"Were you one of those naughty boys or girls who got themselves written up in the Year Book of -?-?-? under the title of Scandal?" -staged photograph of couple kissing, circa 1927 - Munro, Melville S. (Tufts Archival Research Center, 2005)
6 x 5, mounted on 8 x 10 in: M. S. Munro, Miscellaneous pictures through the years, Vol. 1, p. 16